Tax Incentives in Cambodia - Ghazanchyan, Manuk; Klemm, Alexander; Zhou, Yong Sarah (Washington, D.C. : International Monetary Fund, 2018)
Cambodia, like its regional peers, offers a number of tax incentives to investors. This paper reviews these incentives to assess their costs and benefits, including their likely effectiveness in attracting capital and in supporting the diversification strategy. It finds that an important incentive, the tax holiday, differs materially from practice elsewhere in offering a deferral rather than exempting from tax and may not be very effective. Moreover, other features of the tax system, such as the high withholding rate on dividends, imply relatively high effective tax rates for foreign investors. The paper discusses potential reforms that weigh revenue and other costs of tax incentives against the need for a competitive tax system, including a shift from tax holidays toward investment allowances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet